CONSTRUCTIVIST APPROACH TO THE TEACHING OF ENGLISH FOR TOURISM STUDENTS - Dias, Naveen A. H (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Constructivism is ‘an approach to learning that holds that people actively construct or make their own knowledge and that reality is determined by the experiences of the learner’ (Elliott et al. 256). Dewey in his book, Experience and Education mentions clearly that learning is a social activity - it is something individuals do together, in interaction with each other, rather than an abstract concept.